Association between mental health and academic performance among university undergraduates: The interacting role of lifestyle behaviors. Issue 1 (10th September 2022) - Chu, Tianshu; Liu, Xin; Takayanagi, Shigemi; Matsushita, Tomoko; Kishimoto, Hiro
Abstract: Objectives: Impaired mental health status tends to be associated with poor academic performance, but few prospective studies have examined the association between mental health and academic performance among undergraduates while considering the interacting roles of multiple lifestyle behaviors. Participants and Methods: A total of 1823 Japanese undergraduate students (67% men) were followed up for 4 years. Their mental health status was measured by the six‐item Kessler Psychological Distress Scale (K6). We defined poor academic performance as a grade point average (GPA) <2.0. Cox proportional hazards models were used to determine the relationship between the students' mental health status and the incident risk of poor academic performance. Results: Our analyses revealed that impaired mental health status in the first semester of university study significantly predicted an increased incident risk of poor academic performance during the overall undergraduate period. This association remained significant when the health lifestyle behaviors were adjusted, and the hazard ratio (95% confidence interval) for poor academic performance was 1.62 (1.18–2.23). This significant association disappeared in the low‐lifestyle‐behavior‐risk group. Conclusion: Impaired mental health status in the first semester significantly predicts an increased incident risk of poor academic performance during the undergraduate period.